Rethinking Urban Greening: Implications of Crime Prevention Through Environmental Design for Enhancing Perceived Safety in Baitashan Park, Lanzhou - Fei Hou; Massoomeh Hedayati Marzbali; Mohammad Javad Maghsoodi Tilaki; Aldrin Abdullah (Urban Science)
While urban greening is an effective adaptation strategy for building resilient cities, socioeconomic factors and individual perceptions of urban parks play a significant role in enhancing their safety and inclusiveness. Crime Prevention through Environmental Design (CPTED) is a widely recognized approach for enhancing safety in urban public spaces. However, existing research has largely overlooked the impact of socioeconomic factors and interpersonal needs on shaping perceptions of safety. Baitashan Park is Located in Lanzhou City, Gansu Province, China. It is an iconic urban park with significant cultural and recreational value. Despite the park’s popularity, it faces challenges such as uneven accessibility, maintenance discrepancies, and perceived safety concerns, especially among users from the lower socioeconomic status (SES) group. This study examines how SES and interpersonal needs affect the relationship between CPTED principles and perceived safety. Our findings reveal that interpersonal needs significantly mediate the impact of CPTED on perceived safety, with SES playing a moderating role in both the direct and indirect effects. Specifically, the influence of CPTED on perceived safety through interpersonal needs is more pronounced for individuals with higher SES, while the direct effect of CPTED on perceived safety is also stronger for users with higher SES. These results suggest that the effectiveness of CPTED principles can be enhanced by considering the interplay between socioeconomic status and interpersonal dynamics. This study underscores the importance of adopting a holistic approach to urban park design, integrating environmental, social, and economic factors to promote safety, inclusivity, and well-being for all park users.